The Strategy of Public Services Through Digitalization in Indonesia: A Comparative Study from South Korea Success Story - Dwi Lina Arifianti; Eko Sakapurnama (Journal La Sociale, 2024)
This article provides an overview of the current conditions of digitalizing public services in Indonesia. Rapid transformation in information technology has created opportunities to simplify bureaucratic processes through digitalization. This research analyses public services through digitalization and their potential in the future, comparing them with successful stories in South Korea. Through a comparative study, this study aims to identify best practices in overcoming the gaps and challenges in digitalizing public services. This study uses a qualitative approach by collecting comprehensive literature review data, government reports, and other relevant secondary data. A comparative analysis of Korea's digitalization efforts was conducted to gain insight into potential lessons and best practices. The research results show that the digitalization of public services in Indonesia has large ambitions. However, it still needs to catch up to Korea regarding implementation strategies and the design of digital government principles. Prioritizing digitalization in public services increases the effectiveness and efficiency of public services and equalizes society's quality of life.